EVALUATION OF CRITERIA FOR THE ACTIVITIES OF REPRESENTATIVE OFFICES OF JAPANESE COMPANIES IN THE RUSSIAN FEDERATION AND THE NEED TO IMPROVE THEIR EFFICIENCY - Petrov A. M.; Sembieva L. M.; Golysheva N. I.; Ivanov R. A.; Muravitskaya N. K. (Scientific Journal of Pedagogy and Economics, 2021)
Being one of the most important tools of the national economy, foreign direct investment provides means for production expansion, creating employment opportunities and jobs, accelerating structural changes, improving the country’s financial standing in foreign relations, increasing its foreign exchange reserves, reducing budget holdbacks, and improving its credit rating. In Russia, foreign investments are primarily made through capital contributions by registered foreign residents. According to official reports, in the total annual capital inflows into the Russian Federation, 10 to 12% are attributable to foreign direct investment, 1 to 2% - to indirect investment, and up to 80% - to other investments. The current state of the world economy is characterized by many challenges: from increased competition and a new round of trade wars between major economic powers to a shift in emphasis in approaches to assessing the effectiveness of economic entities from exclusively financial to mainly non-financial, including environmental and social aspects. The corresponding economic conditions, coupled with significant political and economic pressure from a number of countries, sharply raise the issue of developing new approaches to determining the effectiveness of their own activities. Determining the effectiveness of business entities is necessary in order to ensure timely and adequate assessment of their business model from the perspective of key stakeholders and to develop an effective strategy for long-term sustainable functioning in the new business environment.